Book Reviews (The Australian journal of anthropology, 1984)
Book reviewed in this article: People Without Government. An Anthropology of Anarchism. By Harold Barclay The Anarchists of Casas Viejas. By Jerome R. Mintz Hermeneutics and the Human Sciences. Essays on Language, Action and Interpretation. By Paul Ricoeur. Edited, translated and introduced by John B. Thompson The Anthropological Circle. Symbol, Function, History. By Marc Auge Sciences and Cultures. Anthropological and Historical Studies of the Sciences. Edited by Everett Mendelsohn and Yehuda Elkana Australian Sociologies. By Diane J. Austin. George Allen & Unwin Social Inequality in Australian Society. By John S. Western Which Way Is Up? Essays on Class, Sex and Culture. By R. W. Connell. George Allen and Unwin The Australian Journal of Historical Archaeology, Volume 1, January 1983. Edited by Graham E. Connah Pacific Cultural Material in New Zealand Museums. By Roger Neich A Prehistory of Australia, New Guinea and Sahul. By Peter White with James F. Connell The Alligator Rivers: Prehistory and Ecology in Western Arnhem Land. By Carmel Schrire Reward and Punishment in Arnhemland 1962–1963. By Edgar Wells Daughters of the Dreaming. By Diane Bell We Are Bosses Ourselves. The Status and Role of Aboriginal Women Today. Edited by Fay Gale Sorcerers and Healing Spirits. Continuity and Change in an Aboriginal Medical System. By Janice Reid Languages of Kinship in Aboriginal Australia. Edited by Jeffrey Heath, Francesca Merlan and Alan Rumsey Searching for Aboriginal Languages: Memoirs of a Field Worker. By Bob Dixon Vanuatu: Politics, Economics and Ritual in Island Melanesia. Edited by Michael Allen Gifts and Commodities. By C. A. Gregory The Political Economy of the South Pacific. By Michael C. Howard To Find the Baruya Story. A film by Allison and Marek Jablonko and Stephen Olsson. Her Name Came on Arrows. A film by Allison and Marek Jablonko and Stephen Olsson.